2017
DOI: 10.1093/toxsci/kfx061
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Cessation During Adulthood Did Not Prevent Immunotoxicity Caused by Developmental Exposure to Low-Level Trichloroethylene in Drinking Water

Abstract: Exposure to the water pollutant trichloroethylene (TCE) can promote autoimmunity in both humans and rodents. Using a mouse model we have shown that chronic adult exposure to TCE at 500 μg/ml in drinking water generates autoimmune hepatitis in female MRL+/+ mice. There is increasing evidence that developmental exposure to certain chemicals can be more toxic than adult exposure. This study was designed to test whether exposure to a much lower level of TCE (0.05 μg/ml) during gestation, lactation, and early life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
(43 reference statements)
2
16
0
Order By: Relevance
“…As shown by ourselves and others, TCE exposure increased the percentage of IFN-γ-and IL- More recently, our lab demonstrated that continuous exposure to levels of TCE described here was sufficient to promote autoimmune disease in female mice at PND259. Remarkably, the autoimmunity in the form of AIH tissue pathology and anti-liver antibodies was detected 15 weeks after exposure ended, indicating that removal of TCE does not prevent immune-mediated liver pathology (Gilbert et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…As shown by ourselves and others, TCE exposure increased the percentage of IFN-γ-and IL- More recently, our lab demonstrated that continuous exposure to levels of TCE described here was sufficient to promote autoimmune disease in female mice at PND259. Remarkably, the autoimmunity in the form of AIH tissue pathology and anti-liver antibodies was detected 15 weeks after exposure ended, indicating that removal of TCE does not prevent immune-mediated liver pathology (Gilbert et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…More recently, our lab demonstrated that continuous exposure to levels of TCE described here was sufficient to promote autoimmune disease in female mice at PND259. Remarkably, the autoimmunity in the form of AIH tissue pathology and anti‐liver antibodies was detected 15 weeks after exposure ended, indicating that removal of TCE does not prevent immune‐mediated liver pathology (Gilbert et al, ). Given the correlation between gut dysbiosis and autoimmunity, our goal in the current study was to expand this research to assess the impact of developmental TCE exposure on the gut microbiome and gut‐associated immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, reports from human population studies show that prenatal and early postnatal exposure to certain pollutants correlates with immune dysregulation later in life [ 1 4 ]. Research in animal models further supports the idea that immune function at maturity is influenced by early life exposures [ 5 9 ], and that the developing immune system is more sensitive than the mature immune system to enduring modulation by environmental factors [ 10 12 ]. While these studies reveal links between developmental exposures and life-long changes in immune function, how early life exposures shape the immune system is not fully understood.…”
Section: Introductionmentioning
confidence: 97%